Biomimetic encapsulant : purification and self-assembly of natural coiled-coil proteins from marine snail Busycotypus canaliculatus egg case membranes - Tan, Delford Kang Hong (2013)
Due to the harsh environment of its natural habitat, the eggs of Busycotypus canaliculatus have developed a unique shock-absorbing property, protecting the embryos from harm. This material is of interest in the biomimetic materials engineering field as a bio-encapsulant as its properties make it suitable for the protection of delicate cells and tissues during transplantation. This project aims to study the egg capsules of the Busycotypus canaliculatus in order to understand the self-assembly process of the egg capsule proteins. Purification of the capsule proteins was carried out using the high performance liquid chromatography, while characterisation of the proteins was done with mass spectroscopy. The structure of the egg capsules was investigated with scanning electron microscopy and fourier transform infrared microscopy. Purification of the capsule proteins was largely successful, although further work is needed to obtain purified samples of all four capsule proteins. The images from scanning electron microscopy revealed banding patterns reminiscent of collagen fibre bandings, while fourier transform infrared microscopy shed light on the composition of the secondary structures in the capsule proteins.